Role of Savings in Economic Growth of Pakistan - Chandio, Abbas Ali; Wei, Feng; Yuansheng, Jiang (Asian Journal of Empirical Research, 2015)
This empirical study aims to examine the relationship between savings and economic growth of Pakistan over the period 1977-2013. Using the autoregressive distributed lag (ARDL) approach to co-integration, the results show that the empirical evidence strongly suggests that domestic savings played important role in economic growth and development of Pakistan in the long-run. The long-run and short-run elasticity of savings are estimated to be 3.072 and 2.071 respectively. Thus, domestic saving is positively and significantly associated to growth in Pakistan.